Relationship Management and Leadership Effectiveness of Medical Doctors in Benin City, Edo State, Nigeria - Alika, Rhoda Akhere; Dania, Omoyebagbe Rosaline (NIU Journal of Management Sciences, 2026)
Relationship management is a critical interpersonal competency that enables individuals to establish, maintain, and sustain effective relationships within organisational settings. This study is focused on relationship management as a predictor of leadership effectiveness. Specifically, it empirically investigated the impact of relationship management on leadership effectiveness among medical doctors in selected hospitals in Benin City, Edo State. The study population consisted of one thousand four hundred and forty-nine (1449) medical doctors comprising of consultants, resident doctors, medical doctors, and house officers. While the sample size of this study was originally determined to be 313 based on the formula of Taro Yamane (1967), a final sample of 315 medical doctors successfully responded to the study questionnaire. Three hundred and fifteen (315) modified pre-validated structured questionnaires were utilised to draw data from medical doctors in the University of Benin Teaching Hospital (UBTH) and the Edo Specialist Hospital (ESH), Edo State. With the aid of Statistical Package for Social Sciences version 24, data retrieved was analysed using descriptive statistics and regression analysis. Findings revealed that relationship management had a positive and significant impact on leadership effectiveness among medical doctors, as indicated by a p-value of 0.001. Based on the findings, the study recommends that hospital directorates should design and deploy structured leadership development frameworks specifically tailored to cultivate interpersonal competencies.  Also, relationship management competencies should be formally integrated into residency training and continuous professional development (CPD) modules. Keywords: Leadership Effectiveness, Relationship Management, Medical Doctors, Healthcare Institution, Edo State.